Issues towards Efficient Time Synchronization in Wireless Sensor Networks - Abdul Waheed Khan; Abdul Hanan Abdullah; Javed Iqbal Bangash (Institute of Advanced Engineering and Science, 2014)
Wireless sensor network (WSN) is considered as the enabling technology to increase coordination between the physical and virtual worlds. A typical WSN is composed of a large number of computing devices known as nodes which are responsible for sensing and reporting some phenomenon to a sink or base-station where some useful conclusions are drawn from the reported data. Most of the times, the sensed data is of limited usage if not accompanied with timestamp and position information. In addition, several other basic operations in WSNs are based on efficient time synchronization such as duplicate detection, data aggregation/fusion, energy management, transmission scheduling, and cryptography etc; therefore time synchronization plays a pivotal role in operational activities of the network. In this paper, we discuss all the related issues and challenges that revolve around time synchronization in WSNs. Our purpose in writing this paper is to provide an in-depth understanding of the clock synchronization problem in WSNs so that the application designers can fine tune their applications in accordance with the underlined constraints and complexities involved.